ChemInform Abstract: The "Quiet Goldschmidt" — A Mechanochemical, Thermoanalytical, and Spectroscopic Study of Selected Steps of the Aluminothermic Reaction. Issue 31 (11th July 2013) - Stoesser, R.; Feist, M.; Willgeroth, C.; Emmerling, F.; Menzel, M.; Reuther, H.
Abstract The aluminothermic reaction 2Al + α‐Fe2O3 (Goldschmidt reaction) is investigated by powder XRD, ESR and Moessbauer spectroscopy, magnetic susceptibility measurements, and thermal analysis.